Ground-to-satellite quantum teleportation - Ren, Ji-Gang; Xu, Ping; Yong, Hai-Lin; Zhang, Liang; Liao, Sheng-Kai; Yin, Juan; Liu, Wei-Yue; Cai, Wen-Qi; Yang, Meng; Li, Li; Yang, Kui-Xing; Han, Xuan; et al. (Nature (London), 2017)
Quantum teleportation of single-photon qubits from a ground observatory to a satellite in low-Earth orbit via an uplink channel is achieved with a fidelity that is well above the classical limit. Quantum security in orbit The laws of quantum physics give rise to protocols for ultra-secure cryptography and quantum communications. However, to be useful in a global network, these protocols will have to function with satellites. Extending existing protocols to such long distances poses a tremendous experimental challenge. Researchers led by Jian-Wei Pan present a pair of papers in this issue that take steps toward a global quantum network, using the low-Earth-orbit satellite Micius. They demonstrate satellite-to-ground quantum key distribution, an integral part of quantum cryptosystems, at kilohertz rates over 1,200 kilometres, and report quantum teleportation of a single-photon qubit over 1,400 kilometres. Quantum teleportation is the transfer of the exact state of a quantum object from one place to another, without physical travelling of the object itself, and is a central process in many quantum communication protocols. These two experiments suggest that Micius could become the first component in a global quantum internet. An arbitrary unknown quantum state cannot be measured precisely or replicated perfectly 1 . However, quantum teleportation enables unknown quantum states to be transferred reliably from one object to another over long distances 2 , without physical travelling of the object itself. Long-distance teleportation is a fundamental element of protocols such as large-scale quantum networks 3 , 4 and distributed quantum computation 5 , 6 . But the distances over which transmission was achieved in previous teleportation experiments, which used optical fibres and terrestrial free-space channels 7 , 8 , 9 , 10 , 11 , 12 , were limited to about 100 kilometres, owing to the photon loss of these channels. To realize a global-scale ‘quantum internet’ 13 the range of quantum teleportation needs to be greatly extended. A promising way of doing so involves using satellite platforms and space-based links, which can connect two remote points on Earth with greatly reduced channel loss because most of the propagation path of the photons is in empty space. Here we report quantum teleportation of independent single-photon qubits from a ground observatory to a low-Earth-orbit satellite, through an uplink channel, over distances of up to 1,400 kilometres. To optimize the efficiency of the link and to counter the atmospheric turbulence in the uplink, we use a compact ultra-bright source of entangled photons, a narrow beam divergence and high-bandwidth and high-accuracy acquiring, pointing and tracking. We demonstrate successful quantum teleportation of six input states in mutually unbiased bases with an average fidelity of 0.80 ± 0.01, well above the optimal state-estimation fidelity on a single copy of a qubit (the classical limit) 14 . Our demonstration of a ground-to-satellite uplink for reliable and ultra-long-distance quantum teleportation is an essential step towards a global-scale quantum internet.